Fucosidosis—Clinical Manifestation, Long-Term Outcomes, and Genetic Profile—Review and Case Series - Stepien, Karolina M. (Genes (Basel), 2020)
Fucosidosis is a neurodegenerative disorder which progresses inexorably. Clinical features include coarse facial features, growth retardation, recurrent upper respiratory infections, dysostosis multiplex, and angiokeratoma corporis diffusum. Fucosidosis is caused by mutations in the FUCA1 gene resulting in α-L-fucosidase deficiency. Only 36 pathogenic variants in the FUCA1 gene are related to fucosidosis. Most of them are missense/nonsense substitutions; six missense and 11 nonsense mutations. Among deletions there were eight small and five gross changes. So far, only three splice site variants have been described—one small deletion, one complete deletion and one stop-loss mutation. The disease has a significant clinical variability, the cause of which is not well understood. The genotype–phenotype correlation has not been well defined. This review describes the genetic profile and clinical manifestations of fucosidosis in pediatric and adult cases.